(untitled) (London Journal of Medical and Health Research, 2024)
Our gastrointestinal system, which is named as our second brain, is struggling with the devastating disease of recentyears, COVID-19. Thestruggle of bacteria in the intestinal microflora in terms of over coming possible liver damage causedby COVID-19 is the subject of researchers. Despite the limited number of studies, the fight againstl iver organ damage by the gastrointestinal system, which is our second brain is important.